Sistem Informasi Rekam Medis Berbasis Web Dengan Framework Laravel Pada Klinik Restu Sehat Serang Baru - Sanudin Sanudin; Agung Rahmawan; Arif Siswandi (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Restu Sehat Clinic is an institution that participates in providing comprehensive and integrated health services to the community in the South Serang Baru area. There are limitations in processing patient data and medical records. Medical record is a file that contains records and documents about the patient's identity, examination, treatment, actions, and services that have been provided to patients. The process of processing patient information at the Restu Sehat Clinic is still manual, which is recorded in a book which causes several obstacles to overcome this, result of this analysis is the need for an electronic medical record information system. The method used to build an electronic medical record information system is by using the prototype method, the design is carried out using UML (Unified Modeling Language) and coding the system using the PHP (Hypertext Preprocessor) programming language with the Laravel 8 Framework. With the existence of an electronic medical record information system, will make it easier to manage patient medical record data and reduce the risk of losing patient data. Keyword: Clinic, Medical Record, Prototype, UML, PHP, Laravel 8.